Institutional Determinants Of Sectoral FDI In Eastern European And Central Asian Countries : The Role Of Investment Climate And Democracy - Doytch, Nadia; Eren, Mesut (M E Sharpe Inc, 80 Business Park Dr, Armonk, Ny 10504 Usa, 2012)
We study the determinants of the sectoral distribution of foreign direct investment (FDI) in Eastern Europe and Central Asia, focusing on the investment climate and state of democracy. Using a dynamic system generalized method of moments estimator, we examine twenty-one countries for the period 1994-2008. We find that when human capital is controlled for, the host country investment profile has a positive effect on agricultural FDI and the host country state of democracy positively affects agricultural and manufacturing FDI. In addition, services FDI is attracted by educated labor, whereas FDI to other sectors is attracted by cheap labor. Moreover, natural resource endowments have a positive impact on FDI in the sectors of agriculture and manufacturing.
Keywords: Democratic Accountability; Institutional Determinants; Investment Profile; Sectoral FDI; Foreign Direct-investment; Real Exchange-rate; United-States; Tax Policy; Panel-Data; Corruption; Rates; Governance; Patterns; Decision; Demokratik Hesap; Kurumsal Belirleyicileri; Yatırım Profili; Sektörel DYY; Doğrudan Yabancı Yatırım; Reel Döviz Kuru; Birleşik Devletleri; Vergi Politikası; Panel Verisi; Rüşvet; Oranlar; Yönetim; Desenler; Karar